2012
DOI: 10.1128/jcm.05821-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinically Relevant Corynebacterium spp., Arcanobacterium haemolyticum, and Rhodococcus equi by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: The identification of 83 Corynebacterium, 13 Arcanobacterium haemolyticum, and 10 Rhodococcus equi strains by conventional methods (API Coryne complemented with 16S rRNA gene sequence analysis) was compared with matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry identification. The correlation between API and MALDI-TOF results was 89%. MALDI-TOF is a rapid and accurate system for identification of the above-mentioned microorganisms. Corynebacteria are widespread throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
4
28
0
2
Order By: Relevance
“…Identification rates for the direct transfer-formic acid method were comparable to those of the ethanol-formic acid extraction procedure that is considered the gold standard and which is used to generate the reference database. These findings are in agreement with previous reports which indicated that on-target treatment with formic acid or ethanol-formic acid extraction improved identification of GPR by MALDI-TOF MS (13,14,24,26). However, the ethanol-formic acid procedure includes various manual preparation steps and is time-consuming (22).…”
Section: Maldi-tof Ms Is Increasingly Used In Diagnostic Laboratoriessupporting
confidence: 83%
See 1 more Smart Citation
“…Identification rates for the direct transfer-formic acid method were comparable to those of the ethanol-formic acid extraction procedure that is considered the gold standard and which is used to generate the reference database. These findings are in agreement with previous reports which indicated that on-target treatment with formic acid or ethanol-formic acid extraction improved identification of GPR by MALDI-TOF MS (13,14,24,26). However, the ethanol-formic acid procedure includes various manual preparation steps and is time-consuming (22).…”
Section: Maldi-tof Ms Is Increasingly Used In Diagnostic Laboratoriessupporting
confidence: 83%
“…Identification by MALDI-TOF MS has been analyzed for single genera of GPR, such as Corynebacterium (13)(14)(15), Actinomyces (16), Nocardia (17), Listeria (18), anaerobic GPR (19), and difficult-to-identify GPR (20,21). These studies were mostly done using the Bruker MALDI Biotyper system and indicated that sample preparation by the direct transfer procedure without additional modification is not sufficient for accurate identification of GPR but that a chemical extraction method is required.…”
mentioning
confidence: 99%
“…In addition to the reverse CAMP test, the API Coryne test was used to accurately identify A. haemolyticum, as in previous studies (Soto et al, 1994;Hassan et al, 2009;García-de-la-Fuente et al, 2012). As in previous reports, MALDI-TOF MS was also useful for the rapid identification of A. haemolyticum (Hijazin et al, 2012;Vila et al, 2012). The identification of A. haemolyticum strains at the species level was confirmed by the PCR amplification of pld, which encodes phospholipase D.…”
Section: Discussionmentioning
confidence: 99%
“…Concordant results upon direct Gram staining increase the confidence level for an involvement in infection and are useful for retrospective reviews of data sets, but the decision to select isolates for species-level identification by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) in most laboratories is independent of direct Gram stain results. With the advent and incorporation of MALDI-TOF MS in the clinical microbiology laboratory, the majority of these suspicious diphtheroids can now be routinely identified to the species level (7,8).…”
mentioning
confidence: 99%